Evaluasi Hedonik Produk Kopi Biji Salak Jahe Creamy (Salacaffe) dengan Variasi Konsentrasi Jahe - Irmafiyani, Ani; Nalinda, Rika; Puspitojati, Endah (Jurnal Agroteknologi (Agronu), 2025)
This study aimed to evaluate consumer preference for creamy ginger salak seed coffee (Salacaffe) with varying ginger concentrations. The case study in this research focused on salak seed coffee produced by D’Kenthos Coffee, owned by PT Sarisa Merapi Group. Salak seed coffee was a low-caffeine coffee alternative with the potential to become a healthy and innovative beverage. The research involved 100 respondents selected through purposive sampling. An organoleptic test was conducted using a hedonic scale to assess the attributes of texture, color, aroma, taste, and aftertaste. Three formulations with different ginger concentrations (600 g, 800 g, and 1000 g) were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The results indicated no significant differences in texture, color, and aroma attributes, both in powder and brewed form. However, significant differences were found in the taste and aftertaste attributes, where the formulation with 800 g of ginger received the highest preference due to its balanced spiciness and pleasant aftertaste. This study demonstrated that varying ginger concentrations in creamy ginger salak seed coffee could influence panelist preference, particularly in terms of taste and aftertaste. The formulation with 800 g of ginger was recommended for further development as a creamy ginger salak seed coffee (Salacaffe) beverage product